Physical characteristics of jackfruit at different harvesting times - Irin, IJ; Haque, MA; Rabbani, MG; Biswas, PK (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Jackfruit Research Project, Horticulture farm of Bangladesh Agricultural University, Mymensingh during the period from December 2002 to July 2003 with the objectives to determine the physical characteristics of three types of jackfruit at different harvesting time vis a vis appropriate time of harvest of them. Physical craracteristics of three types indicated that bulb weight (%) decreased and rind weight (%) increased at later stages of harvesting. The bulb of Ghila was very soft at early harvesting stage but firm at late harvesting. The edible portion was found to be the highest (59.95%) in mid harvesting time and Dorosha type gave the maximum (55.21%). The fruits of late harvesting time had viviparous seed. Early and mid harvesting times were found to be better in all three types of Jackfruit and Ghila was found to be superior. Bangladesh Agron. J. 2014, 17(2): 89-94